Multiple barcode assessment within the Saprolegnia-Achlya clade (Saprolegniales, Oomycota, Straminipila) brings order in a neglected group of pathogens - Steciow, Mónica Mirta (2014)
The Saprolegnia-Achlya clade comprises species of major environmental and economic importance due to their negative impact on aquaculture and aquatic ecosystems by threatening fishes, amphibians, and crustaceans. However, their taxonomy and phylogenetic relationships remain unresolved and suffer from many inconsistencies, which is a major obstacle to the widespread application of molecular barcoding to identify pathogenic strains with quarantine implications. We assessed phylogenetic relationships of major genera using three commonly used markers (ITS, SSU rRNA, and LSU rRNA). A consensus tree of the three genes provided support for nine clades encompassing eleven documented genera and a new clade (SAP1) that has not been described morphologically. In the course of this study, we isolated a new species, Newbya dichotoma sp. nov., which provided the only culture available for this genus. In parallel, we attempted to summarize the evolution of traits in the different genera, but their successive reversals rendered the inference of ancestral states impossible. This highlights even more the importance of a bar-coding strategy for saprolegniacean parasite detection and monitoring.